Yam Cropping System in Cote d’Ivoire: Current Practices and Constraints - Amani Michel Kouakou; Guy Fernand Yao; Konan Evrard Brice Dibi; Adolphe Mahyao; Antonio Lopez-Montes; Brice Sidoine Essis; Boni N’zue; Brou Kouamé; Patrick Olusanmi Adebola; Asrat Asfaw; Robert Asiedu (European Scientific Journal, ESJ, 2019)
Yam is the first food crop in Côte d'Ivoire. It is being cultivated under a traditional technique system with low output. Detailed profiling of the current practices and opportunities for improvement is essential to increase the benefits of yam for food security and income in the country. This study diagnosed the current practices, constraints, and requirements in order to gain insight on the yam cropping system for research and development in Côte d'Ivoire. The surveys were conducted in seven (7) regions in the main yam production area. Groups of 60 producers per region were investigated. Individual surveys were also conducted on-farm, particularly for diagnosing the physical environment and yam-based production systems. As results, yambased production systems are characterized by mixed cropping (cassava, corn and vegetable crops) and/or rotation with various other crops (rice, groundnut, vegetable crops, …). Preferred plots for yam cultivation are forest, savannah or fallow areas. The major constraints in yam cultivation were the effects of environmental stresses, labor scarcity, pest damage, tuber and seed storage difficulties as well as the low market value of yam. The most cultivated yam varieties are Bètè-Bètè and Florido for Dioscorea alata and Lokpa for Dioscorea rotundata. The cropping system, the species and varieties vary according to the region, the topo sequence and the type of soil. Knowledgebuilding that take into account constraints related to yam cultivation, for each production area, can serve as guidance for variety breeding and cultivation environment redefinition.